Epidemiology, clinical outcomes, and treatment patterns of cytomegalovirus infection after allogeneic hematopoietic stem cell transplantation in China: a scoping review and meta-analysis - Lin, Ren; Wu, Jingyi; Liu, Qifa (Frontiers in Microbiology, 2025)
IntroductionCytomegalovirus (CMV) infection poses a significant threat to individuals undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT), potentially resulting in substantial morbidity and mortality. This review summarized the epidemiology, clinical outcomes, and treatment patterns of CMV infection among allo-HSCT recipients in China.MethodsPubMed, EMBASE, the Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang and Chinese Biomedical Literature Database (CBM) were systematically searched from 2013 to March 2023. All analyses were performed using R 4.1.1 software with a random effects model.ResultsFifty-six studies, which included 13,882 patients, were reviewed. The pooled overall incidence of CMV infection was 49.99% [95% confidence interval (CI) 43.72–56.26%]. Among post allo-HSCT recipients with CMV infection, 32.03% (95% CI 22.93–41.12%) developed refractory CMV infection. The overall incidence of CMV disease was 13.30% (95% CI 8.99–19.66%). The pooled all-cause mortality rate was 29.25% (95% CI 17.96–40.55%) and the CMV-related mortality rate was 3.46% (95% CI 1.19–5.73%). Results demonstrate that management of CMV has mainly focused on pre-emptive therapy due to the treatment-limiting toxicity of anti-CMV agents. Additionally, CMV infection is continuing to occur after the discontinuation of prophylaxis, highlighting the unmet need for a more effective treatment without treatment-limiting toxicities.ConclusionThis review underscores the urgent need for improved therapeutic strategies to effectively manage cytomegalovirus infection in allo-HSCT recipients, particularly in light of the high incidence and associated morbidity, as well as the limitations of current treatment options.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024513908, identifier: CRD42024513908.